THE MEDICINAL PROPERTIES OF THE MEDICINAL LAVENDER PLANT, AS WELL AS ITS PESTS AND MEASURES TO COMBAT THEM - A.N.Akbutayev (American Journal of Biodiversity, 2024)
In this article, the medicinal properties of the medicinal lavender plant, its pests and measures to combat them.